2015
DOI: 10.1177/1039856215592320
|View full text |Cite
|
Sign up to set email alerts
|

Implementing music therapy on an adolescent inpatient unit: a mixed-methods evaluation of acceptability, experience of participation and perceived impact

Abstract: Integration of music therapy in inpatient treatment of adolescents is feasible and acceptable, and is valued by staff and patients as a complement to 'talking therapies'. Participation is enjoyed and associated with outcomes including improvement in mood, expression of feelings and social engagement consistent with recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 12 publications
2
26
0
1
Order By: Relevance
“…Like the findings of Patterson et al . 's () study in an adolescent unit, consumers in this present study enjoyed participating and benefits were shown in terms of mood, social connectedness and enhanced ward atmosphere. Patterson et al .…”
Section: Discussionmentioning
confidence: 50%
See 4 more Smart Citations
“…Like the findings of Patterson et al . 's () study in an adolescent unit, consumers in this present study enjoyed participating and benefits were shown in terms of mood, social connectedness and enhanced ward atmosphere. Patterson et al .…”
Section: Discussionmentioning
confidence: 50%
“…Few studies have evaluated music therapy from the perspective of the staff. Consistent with the findings from Patterson et al .’ () study with adolescent mental health inpatients, staff in the unit commented favourably on the effect on the ward atmosphere and on their own mood. The positive impact on the ward atmosphere was also noted by consumers.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations